RANCANG BANGUN ALAT PEMANTAUAN PENGATURAN KECEPATAN PUTAR MOTOR DC POWER WINDOWS BERBASIS PLC PANASONIC MENGGUNAKAN HUMAN MACHINE INTERFACE (HMI) - Anarwati, Agustin; Setiono, Iman (Gema Teknologi, 2017)
Agustin Anarwati, Iman Setiono, today human life is very rapidly developing, one of them in the field of technology as time advances. This requires the creation of ideas to make a variety of equipment that is more practical and more reliable in meeting needs. In the industrial world today, most equipment uses PLC as a controller for various existing equipment, while the Human Machine Interface (HMI) is used to simplify monitoring existing equipment. In the automotive world, the power windows system is part of the body's electrical circuit which aims to make it easier for motorists to operate car windows. The driver can adjust the work of the power windows through a switch. When the driver presses the switch then the motor power window will rotate and will make the window work both open and close. The type of motor used in the power window system is a DC motor. One of the features of this DC motor is its speed can be controlled easily. In this case, I tried to make the design of the monitoring device setting the DC power speed of the windows power using PLC and HMI as monitors and controllers for operating the DC power windows rotating speed to make it easier, the speed can be adjusted through the output voltage from the PLC to the driver, starting from 0 VDC up to 5 VDC. if the voltage is 5 VDC then the motor will rotate with a maximum speed of 100%, whereas if given a 2.5 VDC input, the motor speed will be half of the 5 VDC rotational speed.